2012
DOI: 10.1097/hjh.0b013e328352573b
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy soluble E-selectin concentrations and risk of preeclampsia

Abstract: Changes in soluble E-selectin concentration in early pregnancy may reflect underlying pathophysiological processes, potentially providing mechanistic insights into preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…It therefore appears plausible, although not directly proven in this cross-sectional study, that effects of impaired renal function on vascular stiffness are at least in part mediated by increased levels of E-selectin. We have previously demonstrated a role of E-selectin in the early stages of pre-eclampsia, a condition that is also associated with renal damage and endothelial dysfunction [24]. Other studies [25,26] reported that adhesion molecules are independent predictors of cardiovascular events in patients with ESRD, although not all studies confirm these data [27].…”
Section: Discussionmentioning
confidence: 99%
“…It therefore appears plausible, although not directly proven in this cross-sectional study, that effects of impaired renal function on vascular stiffness are at least in part mediated by increased levels of E-selectin. We have previously demonstrated a role of E-selectin in the early stages of pre-eclampsia, a condition that is also associated with renal damage and endothelial dysfunction [24]. Other studies [25,26] reported that adhesion molecules are independent predictors of cardiovascular events in patients with ESRD, although not all studies confirm these data [27].…”
Section: Discussionmentioning
confidence: 99%
“…In France, Bretelle et al and Bersinger et al in Switzerland reported similar results in increasing Eselectin in PE (15,16). In Carty DM et al study, E-selectin concentrations were higher in women who develop PE in preterm labor lower than 28 weeks (8). Against to these results, Phocas et al (17) and Chaiworapongsa et al (6) could not detect an increased E-selectin serum level in PE.…”
Section: Resultsmentioning
confidence: 86%
“…Cellular forms of adhesion molecules mediate specific steps of leukocyte-endothelial cell interaction and have been implicated in the pathophysiology of PE (6). Adhesion molecules, such as E-selectin (produced by endothelial cells) is an inflammatory biomarker (4) and has been shown to correlate with the level of oxidative stress in preeclampsia (7,8). Soluble forms of these molecules can be detected in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide dismutase (SOD), catalase (Cat) and glutathione peroxidase (GSH) play important roles in counteracting oxidative stress (24,25).Oxidative agents are overproduced due to ischaemicreperfusion injury and may overwhelm potential antioxidant activity (26,27,28). Additionally, adhesion molecules, such as E-selectin (produced by endothelial cells) and P-selectin (found in a-granules of platelets), have been shown to correlate with the level of oxidative stress in pregnancy (29). To the best of our knowledge, many pregnancy complications and birth defects have been linked to oxidative stress, free radical damage and low GSH levels in the mother and fetus.GSH and other antioxidants attenuate oxidative stress in pregnant women with inflammation or maternal conditions like PE, The GSH also prevents or minimizes the oxidative stress that occurs during labor and the birth process (30).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%